University social responsibility: The case of Italy - Maurizio Comoli; Lorenzo Gelmini; Valentina Minutiello; Patrizia Tettamanzi (Administrative Sciences, 2021)
Increasing attention is now being paid to the concept of sustainability as a crucial element of our life at all levels. The awareness that attention must be paid not only to the present, but also and above all to the future of the society in which we live has increased attention to social and environmental issues, such as climate change and the digital revolution. This transformation has also impacted the public sector: in particular, the scientific attention in the university sector has led to the birth of the concept of University Social Responsibility (USR), which suggests that universities sustainably re-transform their work. However, this issue has so far only been the subject of a few studies. The purpose of this article is to promote greater awareness on the part of universities of the importance of addressing sustainability issues. The results of the analysis, obtained thanks to the use of a questionnaire and interviews, depict the state of the art in the adoption of social reporting practices by Italian universities and identify the main reasons and barriers to the adoption of these practices.
Keywords: 350; Italy; universities; university social responsibility; CSR reporting; social responsibility